AFLP-AFLP in silico-NGS approach reveals polymorphisms in repetitive elements in the malignant genome - Koblihova, Jitka; Srutova, Klara; Krutska, Monika; Klamova, Hana; Machova Polakova, Katerina (PLoS One, 2018)
The increasing interest in exploring the human genome and identifying genetic risk factors contributing to the susceptibility to and outcome of diseases has supported the rapid development of genome-wide techniques. However, the large amount of obtained data requires extensive bioinformatics analysis. In this work, we established an approach combining amplified fragment length polymorphism (AFLP), AFLP in silico and next generation sequencing (NGS) methods to map the malignant genome of patients with chronic myeloid leukemia. We compared the unique DNA fingerprints of patients generated by the AFLP technique approach with those of healthy donors to identify AFLP markers associated with the disease and/or the response to treatment with imatinib, a tyrosine kinase inhibitor. Among the statistically significant AFLP markers selected for NGS analysis and virtual fingerprinting, we identified the sequences of three fragments in the region of DNA repeat element OldhAT1, LINE L1M7, LTR MER90, and satellite ALR/Alpha among repetitive elements, which may indicate a role of these non-coding repetitive sequences in hematological malignancy. SNPs leading to the presence/absence of these fragments were confirmed by Sanger sequencing. When evaluating the results of AFLP analysis for some fragments, we faced the frequently discussed size homoplasy, resulting in co-migration of non-identical AFLP fragments that may originate from an insertion/deletion, SNP, somatic mutation anywhere in the genome, or combination thereof. The AFLP-AFLP in silico-NGS procedure represents a smart alternative to microarrays and relatively expensive and bioinformatically challenging whole-genome sequencing to detect the association of variable regions of the human genome with diseases.
Keywords: Amplified Fragment Length Polymorphism Analysis; inhibitory proteinkinas; lidé; mladiství; Adult; Base Sequence; Genome, Human; Middle Aged; DNA fingerprinting; Case-Control Studies; Female; Antineoplastic Agents; repetitivní sekvence nukleových kyselin; protinádorové látky; Computer Simulation; Adolescent; Humans; vysoce účinné nukleotidové sekvenování; imatinib mesylát; chronická myeloidní leukemie; genom lidský; studie případů a kontrol; Computational Biology; High-Throughput Nucleotide Sequencing; výpočetní biologie; Repetitive Sequences, Nucleic Acid; lidé středního věku; DNA, Neoplasm; kohortové studie; Cohort Studies; mužské pohlaví; mladý dospělý; Sequence Analysis, DNA; sekvenční analýza DNA; počítačová simulace; ženské pohlaví; Young Adult; analýza polymorfismu délky amplifikovaných restrikčních fragmentů; DNA nádorová; Aged, 80 and over; Protein Kinase Inhibitors; senioři nad 80 let; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Aged; Male; dospělí; Imatinib Mesylate; DNA Fingerprinting; sekvence nukleotidů; senioři